Physical rehabilitation after a mini-invasive hernia removal in the thoracic spine using the Huber Motion Lab system - Я.Ю. Лисюк (H.S. Skovoroda Kharkiv National Pedagogical University, 2017)
Intervertebral hernia of the thoracic spine, represents a significant threat to human health. In the untimely treatment and implementation of a program of physical rehabilitation of a hernia accompanied by a number of complications that can malignantly affect human life and livelihoods. In this paper, the effectiveness of conducting physical rehabilitation after the mini-invasive removal of intervertebral hernia in the thoracic spine with the help of the computerized system of HUBER Motion Lab, which has a wide range of applications for the restoration of people with this pathology, is presented. Considered the issues that are needed to ensure the effective use of the program of physical rehabilitation using the HUBER Motion Lab system for hernia in the thoracic spine. The experience gained from the scientific achievements of specialists in the field of physical rehabilitation and modern computerized rehabilitation technologies is considered. The approaches to ensuring the effectiveness of the program of physical rehabilitation are presented.